Spectrophotometric Determination of Cefpodoxime Proxetil - Srinivasa Rao, Y.; Rajani Kumar, V.; Seshagiri Rao, J.V.L.N. (Asian Journal of Chemistry, 2010)
Two simple and reproducible spectrophotometric methods have been developed for the estimation of cefpodoxime proxetil. One of these methods, Method-A is based on the reaction of the drug with a known excess of chloramine-T and the unreacted chloramine-T when made to react with Gallocyanine oxidises it and thereby decreases its colour intensity. The decrease in the colour intensity of the dye solution, which is measured at 515 nm, is proportional to the concentration of the drug. In method B, the drug is treated with a known excess of potassium permanganate and the unreacted permanganate is then nlade to react with Fast Green FCP. Permanganate oxidises the standard dye solution and thereby decreases its colour intensity. The decrease in the colour intensity of the dye solution, which is measured at 625nm. is proportional to the concen tration of the drug.